SISTEM PELAYANAN WISUDA BERBASIS WEB DI UNIVERSITAS SAHID SURAKARTA - Mohan Adha Rifai; Dwi Retnoningsih; Firdhaus Hari Saputro Al Haris (Universitas Sahid Surakarta, 2017)
The quality of an agency can be obtained in various ways such as by improving the quality of employee resources, training/education, structured work management as well as the management and care of good data. Currently, data management is essential for any institution, both government and private agencies, because basically all agencies working process requires data that will be processed and processed in a way to produce a report that will be used in accordance with their respective needs. Sahid University of Surakarta is one example of private educational institutions that need servicing and processing of structured data, such graduation data. Because they are still using semi manual procedure on the sistem, so that need takes a special system to do service graduation. The process of making